Analysis of the 2020 Bebras Indonesia challenge tasks for elementary school level - Vania Natali; Natalia; Mariskha Tri Adithia (Universitas PGRI Pontianak, 2026)
Bebras Challenge (BC) is an international challenge/competition aimed at promoting computational thinking and informatics among school-age students. The implementation of BC in Indonesia has shown that elementary school students’ performance is not yet optimal. This study aims to analyze the appropriateness of the difficulty level of the 2020 Indonesian BC tasks for elementary school students (SiKecil and Siaga categories), as well as to identify words that may hinder students’ comprehension of the BC tasks. The research was conducted through two stages of review involving 27 BC 2020 tasks and eighteen elementary school teachers from diverse backgrounds. The teachers were asked to evaluate the level of task attractiveness, the clarity of the problem statements, the clarity of the solution explanations, and the appropriateness of the difficulty level. They were also invited to provide feedback on vocabulary that might be difficult for students to understand. The statistical analysis indicates that, overall, the difficulty levels of the tasks were appropriate for the intended age categories. However, several terms—both informatics-related and general terms such as horizontal, vertical, and intersecting—were found to potentially hinder students’ comprehension of the BC tasks. Revisions to the BC tasks and their explanations were shown to improve comprehension levels for most of the problems. This study contributes by recommending the involvement of elementary school teachers in reviewing translated tasks before their nationwide implementation and by providing an evaluative basis for improving the quality of Indonesian BC tasks at the elementary school level.